Pengaruh Substitusi Tepung Beras Merah Pada Pembuatan Roti Hot dog Terhadap Sifat Fisik Dan Daya Terima Konsumen - Putra, Fahri Artha; Cahyana, Cucu; Artanti, Guspri Devi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the effect of brown rice flour substitution in making hot dog buns on physical properties and consumer acceptability. The method in this research is experimental method with brown rice flour substitution as much as 10%, 20%, and 30%. Tests include physical properties tests from the aspects of volume and height of bread and consumer acceptance tests in the aspects of volume, skin color, skin characteristics, pore crumb color, crumb texture, bread aroma, sour aroma, taste, chewing quality. The test was conducted on 30 semi trained panelists, namely Tata Boga students. The results of the physical properties test showed that the volume of 10% substitute hot dog buns was closest to the volume of control hot dog buns with an average of 165 cm3. The results of the height of hot dog buns with 10% brown rice flour substitution were closest to the height of the control hot dog buns with an average of 4.9 cm. The results of the Friedman test on the aspects of volume, skin color, crumb color, pores, crumb texture, and chewing quality show that there is an effect of brown rice flour substitution on consumer acceptance. While in the aspects of skin characteristics, bread aroma, sour aroma and taste, it shows that there is no effect of brown rice flour substitution on consumer acceptance. The results of the tuckey test in the aspects of volume, skin color, crumb color, pores, crumb texture and chewing quality show that hot dog bread with 10% substitution treatment is the most preferred by panelists, based on the results of the research that has been done, it can be recommended that hot dog bread products with 10% brown rice flour substitution be produced.